Effects of HIV/AIDS educational intervention on knowledge, attitude and practices for primary school teachers in Bichi local government Kano, Nigeria - Mustapha, Abdu (2016)
Background: Human immunodeficiency virus (HIV) that causes acquired immune deficiency syndrome (AIDS), is a worldwide public health problem. An estimated 35.0 million people are living with HIV/AIDS globally. Nearly one in twenty adults (4.9%) are living with HIV in sub-Saharan Africa, accounting for about 70% of the global burden. Recent survey revealed that prevalence in Nigeria is 4.1%. Despite a relatively low HIV prevalence of 3.4% in Kano state, a large population size and a high fertility rate make Kano state one of the 21+1 states accounting for 70% of the national burden of HIV. Therefore, it is at risk of increased burden and transmission of HIV. The present study aims to evaluate the effectiveness of HIV/AIDS educational intervention program framed on the information-motivation-behavioral skills models among the primary school teachers in Bichi local government area of Kano state, Nigeria. Methodology: Randomized control trial design was utilized to investigate the impact of HIV/AIDS educational intervention on participant’s HIV/AIDS-related knowledge, attitude and practices. Multi-stage random sampling method was used to select 600 respondents. Participants were randomized to either intervention group or control group. An eight-hour HIV/AIDS education program comprising of six structured modules was developed and delivered to intervention group, while the control group received another eight-hour program on carrier development. Validated and reliable structured questionnaire was used for data collection. Data was collected at baseline, immediately for 2 months intervention and 4 months after the intervention, serving as follow up. General linear model (GLM), repeated measure was applied to assess the effectiveness of the intervention. The outcome measures (HIV/AIDS-KAPs) were assessed at baseline, immediately post-intervention (2 months) and 4 months postintervention. Data was analyzed using SPSS version 22.0. Test of significance was set at α level 0.05. Results: Respondents in the intervention group showed significant improvement in HIV/AIDS knowledge, attitude and practices [mean = [10.41 (1.45), posttest 1 mean score = 17.19 (1.49), posttest 2 mean score = 15.00 (0.71), F (2, 3939.580); P < 0.001]: Attitude [mean = 42.90 (1.88), 64.31 (5.35), 60.36 (2.49); F (2, 2360.382), P < 0.001]. Also, practices [mean = 10.46 (1.39), 16.60 (0.99), 14.89 (1.18); F (1,578), P < 0.001]. Conclusion: The HIV/AIDS educational intervention program developed was effective in improving HIV/AIDS knowledge, attitude and practices among primary school teachers in Bichi local government of Kano state, Nigeria.